The Influence of Inflation, Foreign Investment and Receipt of Remittances on the Rupiah Exchange Rate in 2014 – 2018 - Asro Waruwu; Mutiara Rengganis; Khairani Alawiyah Matondang (Indonesian Journal of Advanced Research, 2023)
The purpose of this study was conducted to determine the effect of inflation, foreign investment, and remittances on the rupiah exchange rate in 2014 - 2018. This type of research is a quantitative approach where this data is of secondary data type in the form of time series. This data is taken from BPS and Bank Indonesia websites. This research method is multiple regression with the OLS model assisted by processing with the Eviews application. The results showed that inflation with the rupiah exchange rate was negatively related, where if inflation increased, the rupiah exchange rate weakened and vice versa, foreign investment did not have a significant effect on the exchange rate and remittances had a significant effect on the exchange rate.